1998
DOI: 10.2307/2446533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross proximity on progeny fitness in a rare and a common species of Eupatorium (Asteraceae)

Abstract: Offspring from matings between near neighbors may exhibit lower fitness relative to offspring from more distant matings due to spatial structuring of populations resulting from limited dispersal of pollen and seed. This response, which can be interpreted as inbreeding depression, is studied in the rare species, Eupatorium resinosum, and a closely related congener, E. perfoliatum, through the use of hand pollinations representing three distance classes (near-within a population, far-within a population, and bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 80 publications
2
63
0
1
Order By: Relevance
“…Population structure and reduced fecundity through inbreeding are of critical importance for rare species because their populations tend to be small and opportunities for outcrossing are often limited (Lande 1988;Ellstrand and Elam 1993;Byers 1998;Lande 1995). Studies have shown that the scale of population structure and the extent of its influence on reproduction varies between species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population structure and reduced fecundity through inbreeding are of critical importance for rare species because their populations tend to be small and opportunities for outcrossing are often limited (Lande 1988;Ellstrand and Elam 1993;Byers 1998;Lande 1995). Studies have shown that the scale of population structure and the extent of its influence on reproduction varies between species.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the relationship between outcrossing distance and reproductive performance is of particular importance for rare and endangered species because any decrease in seed production can threaten the species' long-term viability (Ellstrand and Elam 1993;Byers 1998). Because rare plants typically occur in small populations that are vulnerable to local extinction due to a fixation of deleterious alleles (genetic risk of extinction) and to demographic factors (ecological risk of extinction), opportunities for outcrossing may be critical to ensure maintenance of genetic diversity within populations (Lande 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For effective conservation and management, a thorough understanding of the population dynamics of B. plumosa is necessary. Blepharizonia laxa is also of interest as comparisons of rare and common congeners can provide important information for rare plant management (Bevill and Louda, 1999;Pantone et al, 1995) and can illuminate differences that affect comparative abundance (Byers, 1998). Therefore, between 1996 and 2001 demographic and population biology data on B. plumosa and B. laxa were collected.…”
Section: B-2mentioning
confidence: 99%
“…Diferentes estudios han encontrado relación entre la proximidad espacial y el nivel de consanguinidad de los individuos, producto de una dispersión a corta distancia de polen y/o semillas, lo que resulta en poblaciones espacialmente estructuradas (Glaettli et al 2006). Como resultado, el apareamiento entre vecinos puede generar una fertilidad reducida en comparación con apareamientos entre individuos más distantes, debido a un incremento de los niveles de homocigosidad (Byers 1998, Hardner et al 1998, Glaettli et al 2006. De este modo, la polinización cruzada entre individuos genéticamente diferentes (i.e.…”
Section: Introductionunclassified